2006
DOI: 10.1016/j.otohns.2006.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings for Preemptive Analgesia with Inhaled Morphine: Efficacy in Septoplasty and Septorhinoplasty Cases

Abstract: B-3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…It was noted that the first analgesia requirement emerged significantly later in the nebulized morphine group that is231.72 versus 48.75 minutes. No significant difference was detected between the frequency of postoperative nausea or vomiting [28] …”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…It was noted that the first analgesia requirement emerged significantly later in the nebulized morphine group that is231.72 versus 48.75 minutes. No significant difference was detected between the frequency of postoperative nausea or vomiting [28] …”
Section: Resultsmentioning
confidence: 75%
“…However, 7 patients in the nebulized morphine group required additional diazepam because of restlessness [27] . Other authors have shown the possible efficacy of nebulized morphine in pre-emptive analgesia before septoplasty or septorhinoplasty [28] . In their double-blind RCT, Onal et al randomized 80 patients to either nebulized 65 μg/kg morphine or nebulized saline [28] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations